Development and preliminary psychometric characteristics of the PODIUM questionnaire for recreational marathon runners - Larumbe, E.; Perez-Llantada, M.C.; Lopez de la Llave, A.; Buceta, J.M. (Cuadernos de Psicología del Deporte, 2015)
The purpose of this research was to develop a comprehensive and psychometrically adequate measure of recreational marathon runner’s psychological state during the few days and hours prior to the race. The questionnaire was developed in Spanish. In Study 1, Participants were 1060 recreational runners aged 18-67 years. Exploratory factor analysis revealed five dimensions reflective of motivation, self-confidence, anxiety, perceived physical fitness, and perceived social support. In two subsequent studies, the psychometric properties of a refined version of this measure were examined. In study 2, an independent sample of 801 recreational runners (aged 17-63 years) completed the questionnaire. Confirmatory factor analysis and alternative model testing supported a six-factor model. Internal consistency was .72 to .90. In support of construct validity, the self-confidence scale correlated positively with perceived physical fitness, motivation scale correlated positively with social support and self-confidence, and anxiety correlated negatively with motivation and self-confidence factors. In study 3, an independent sample of 22 recreational marathon runners (aged 28-47 years) responded to the PODIUM and MOMS. Additionally, another independent sample of 36 recreational runners (23-57 years) responded the to PODIUM and CSAI-2 scales. In support of concurrent validity of PODIUM, the motivation scale correlated with MOMS, and the anxiety and the self-confidence scales correlated with CSAI-2.